2008
DOI: 10.1007/bf03325149
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fall-related hip fractures in community-dwelling elderly patients according to cognitive status

Abstract: Some differences were observed, according to the cognitive status of elderly patients suffering a hip fracture due to a fall. A high percentage of dementia patients had suffered repeated falls prior to the fall-related hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…These include: balance impairments,45,78 neuromuscular and musculoskeletal impairments,79 fall type,80 fall severity, and fall speed 65. In addition, the presence of ineffective or suboptimal protective responses, along with age-associated strength decreases,81 cognitive impairment,82 and fear of falling, a serious disorder in older people, may increase the risk of falling and fracturing the hip 83. Declines in visual perception, proprioception and/or transient circulatory insufficiencies,68,84 as well as impaired sensory-motor integration functioning,85 and unexpected perturbations are additional determinants.…”
Section: Methodsmentioning
confidence: 99%
“…These include: balance impairments,45,78 neuromuscular and musculoskeletal impairments,79 fall type,80 fall severity, and fall speed 65. In addition, the presence of ineffective or suboptimal protective responses, along with age-associated strength decreases,81 cognitive impairment,82 and fear of falling, a serious disorder in older people, may increase the risk of falling and fracturing the hip 83. Declines in visual perception, proprioception and/or transient circulatory insufficiencies,68,84 as well as impaired sensory-motor integration functioning,85 and unexpected perturbations are additional determinants.…”
Section: Methodsmentioning
confidence: 99%
“…10 Furthermore, individuals with dementia are more likely to fall, are more likely to fall repeatedly, and have a higher likelihood of sustaining a fracture secondary to fall, even when the number of falls are controlled for. [11][12][13] The reasons for this are likely multifactorial. Formiga and colleagues 13 showed that patients presenting with both hip fracture and dementia were more likely to have an intrinsic cause of fall, whereas those without dementia were more likely to have fallen secondary to extrinsic causes.…”
Section: Dementiamentioning
confidence: 99%
“…[11][12][13] The reasons for this are likely multifactorial. Formiga and colleagues 13 showed that patients presenting with both hip fracture and dementia were more likely to have an intrinsic cause of fall, whereas those without dementia were more likely to have fallen secondary to extrinsic causes. This finding may be at least partially explained by cognitive impairment of patients with dementia, which results in gait disturbances.…”
Section: Dementiamentioning
confidence: 99%
“…A study involving patients admitted to six Spanish hospitals due to hip fracture found that those with a prior diagnosis of dementia had suffered a greater number of recurrent falls before the hip fracture leading to admission. 37 Following admission to hospital, patients with dementia and hip fracture present with a high incidence of delirium. Risk factors include older age, severity of functional and cognitive impairment before fracture, pre-existing cerebrovascular or degenerative disease, social isolation and communication difficulties.…”
Section: Introductionmentioning
confidence: 99%